SCHOOL OF FORMALISTS - Mizrabova Jeren Ismailovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article provides a theoretical overview of Formalism as a school of twentieth-century literary criticism focused on the analysis of the internal structure of the literary text. It examines the key principles of Russian Formalism and Anglo- American New Criticism, including the understanding of literature as an autonomous system, the priority of formal linguistic elements, and the concept of literariness. Special attention is given to V. Shklovsky’s idea of “defamiliarization” and the distinction between fabula and syuzhet, as well as R. Jakobson’s contribution to the development of Structuralism through his theory of metaphor and metonymy and the concept of the poetic function of language.